2021
DOI: 10.3389/fneur.2021.765296
|View full text |Cite
|
Sign up to set email alerts
|

Sex Equitable Prehospital Stroke Triage Using Symptom Severity and Teleconsultation

Abstract: Objectives: We aimed to determine whether there are sex differences in prehospital accuracy of the Stockholm Stroke Triage System (SSTS) to predict large artery occlusion (LAO) stroke, and endovascular thrombectomy (EVT), and whether clinical characteristics differ between men and women undergoing “code stroke” ambulance transport.Materials and Methods: This prospective observational study collected data between October 2017 and October 2018. We included 2,905 patients, transported as “code stroke,” by nurse-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Meanwhile, the TN mimic and TN stroke groups did not have a significant sex difference. Importantly, we have previously shown that the SSTS performs equally between women and men, despite mimics being more common, overall, among women ( 15 ).…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, the TN mimic and TN stroke groups did not have a significant sex difference. Importantly, we have previously shown that the SSTS performs equally between women and men, despite mimics being more common, overall, among women ( 15 ).…”
Section: Discussionmentioning
confidence: 89%
“…While numerous studies on performance of aLVO scales in a population of patients with suspected stroke have been published, we found only 1 publication, which reported on sex differences in prehospital triage of patients with suspected stroke. 24 This Swedish prospective observational cohort study included 2905 patients and investigated the Stockholm Stroke Triage System in which assessment of hemiparesis is combined with teleconsultation. No significant sex differences in performance metrics were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The Stockholm Stroke Triage System (SSTS) is a prehospital triage algorithm designed for detection of LAO stroke patients eligible for EVT, implemented in 2017. 9,10 Assessment of hemiparesis is performed by an ambulance nurse, followed by ambulance to hospital teleconsultation for stroke mimic screening and EVT eligibility. Accepted patients bypass the nearest primary stroke centre (PSC) for direct transport to the TSC.…”
Section: Introductionmentioning
confidence: 99%